2016
DOI: 10.1038/nrgastro.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Human mini-guts: new insights into intestinal physiology and host–pathogen interactions

Abstract: The development of indefinitely propagating human ‘mini-guts’ has led to a rapid advance in gastrointestinal research related to transport physiology, developmental biology, pharmacology, and pathophysiology. These mini-guts, also called enteroids or colonoids, are derived from LGR5+ intestinal stem cells isolated from the small intestine or colon. Addition of WNT3A and other growth factors promotes stemness and results in viable, physiologically functional human intestinal or colonic cultures that develop a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
118
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 101 publications
(147 reference statements)
1
118
0
Order By: Relevance
“…Confocal microscopy of fluorescently labeled actin and wheat germ agglutinin (WGA; indicating glycocalyx-rich cell membrane) showed that both conditions resulted in an organized and polarized epithelium (Fig. 1c) consistent with previously published data 13,14 . Enteroid differentiation (five days in DFM) was associated with defined brush border formation demonstrated by apical actin labeling (Fig.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Confocal microscopy of fluorescently labeled actin and wheat germ agglutinin (WGA; indicating glycocalyx-rich cell membrane) showed that both conditions resulted in an organized and polarized epithelium (Fig. 1c) consistent with previously published data 13,14 . Enteroid differentiation (five days in DFM) was associated with defined brush border formation demonstrated by apical actin labeling (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Enteroids and colonoids are reliable human models for the study of viral and bacterial pathogenesis 14,20,21,41,42 . In the present study, we increased the cellular complexity by integrating macrophages to enteroid monolayers with the purpose of interrogating host-pathogen interactions and innate immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, intestinal organoids have been used to study host–pathogen interactions, for example, during Zika virus infection [9]. Importantly, intestinal organoids may also represent an unlimited source of transplantable tissue suitable for regenerative medicine.…”
mentioning
confidence: 99%
“…Despite serving as the primary portal for enterovirus entry into the human host, it remains unknown whether enteroviruses target select cell types within the intestine for their initial replication. An ex vivo model of the human intestinal epithelium has been developed, whereby primary intestinal crypts are isolated and cultured into epithelial structures that have been described as "mini-guts," often termed enteroids (7)(8)(9). Primary intestinal crypts are plated onto Matrigel, mimicking the enriched levels of laminin α1 and α2 present at crypt bases in vivo (10), and are cultured in the presence of growth factors that induce crucial developmental signaling through the Wnt and Notch pathways.…”
mentioning
confidence: 99%